Microbial Transglutaminase Is Immunogenic and Potentially Pathogenic in Pediatric Celiac Disease - Matthias Torsten; Lerner Aaron; Lerner Aaron (Frontiers Media S.A., 2018)
The enzyme microbial transglutaminase is heavily used in the food processing industries to ameliorate food qualities and elongate the products' shelf life. As a protein's glue, it cross-links gliadin peptides, creating neo-complexes that are immunogenic and potentially pathogenic to celiac disease communities. Even lacking sequence identity, it imitates functionally the endogenous tissue transglutaminase, known to be the autoantigen of celiac disease and representing an undisputable key player in celiac disease initiation and progress. The present review expend on the enzyme characteristics, exogenous intestinal sources, its cross-linking avidity to gluten or gliadin, turning naïve protein to immunogenic ones. Several observation on microbial transglutaminase cross linked complexes immunogenicity in celiac patients are reviewed and its pathogenicity is summarized. Warnings on its potential risks for the gluten dependent conditions are highlighted. When substantiated, it might represent a new environmental factor of celiac disease genesis. It is hoped that the presented knowledge will encourage further research to explore the mechanism and the pathogenic pathways taken by the gliadin cross linked enzyme in driving celiac disease.